Assistenzsysteme zur Reduktion des Schädigungsverhaltens von Komponenten einer mobilen Arbeitsmaschine - Brinkschulte, Lars (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2021)
In this work, modular damage reduction assistance systems are investigated. Identification modules provide information about the current driving and working state, the machine operator, the bulk material mass and system parameters. Damage modules with complexity reduced calculation approaches allow a quantification of the machine damage. Possible applications and the potential of the assistance systems are demonstrated in a model-based development environment.